Land Cover Change Prediction and Its Alignment with Regional Spatial Planning in the Coastal Area of Tegal Regency, 2031 - Puspitaningrum, Diyah Pawitri; Wibowo, Afif Ari; Surachman, Dedi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this study is to examine the projected changes in land cover in the Tegal Regency Coastal Area in 2031 and assess how well the Tegal Regency Regional Spatial Plan aligns with the anticipated changes in land cover. Methodology: This research used stratified random sampling method to determine the sample points used. The MOLUSCE plugin in QGIS 2.18.1 was used to simulate the prediction of land cover change. Results: According to the study's findings, there was a 2,120.58 hectare increase in the extent of agricultural land between 2007 and 2015. Similarly, there was a 457.65-hectare increase in built-up land. Additionally, the area of agricultural land grew by 1,069.02 hectares between 2015 and 2023. According to the 2031 land cover prediction, the amount of built-up land increased by 460.26 hectares and the area of agricultural land by 270.00 hectares. The results of the intersection of the Regional Spatial Plan Map and the 2031 Land Cover Prediction Map showed that 72.04% of the land area was suitable, while 27.96% was unsuitable. Applications/Originality/Value: This research can be used as a basis for future decision making because from the results there are several areas that do not match the prediction results and the Spatial Plan Map.